EPIDEMIOLOGICAL ASPECTS OF FELINE TOXOPLASMOSIS - Bresciani, Katia Denise Saraiva; Galvão, André Luiz Baptsta; de Vasconcellos, Amanda Leal; dos Santos, Thaís Rabelo; Kaneto, Carlos Noriyuki; Viol, Milena Araúz; Gomes, Jancarlo Ferreira; Bilsland, Eizabeth (Archives of Veterinary Science, 2016)
Toxoplasmosis is a zoonosis distributed worldwide, which is of great importance in human and veterinary medicine. Toxoplasmosis, caused by Toxoplasma gondii, can be transmitted through the ingestion of tissue cysts in infected meat, ingestion of food or water contaminated with oocysts and congenitally, by tachyzoites crossing the placenta from the infected mother to the fetus. Felines in particular (intermediate or definitive hosts for the parasites) have an important role in the epidemiology of this agent, as they can eliminate oocysts in the domestic environment. The aim of this review is to describe clinical manifestations of toxoplasmosis, to address the role of cats in the spread of the disease, as well as to discuss methods of diagnosis, therapeutic measures, prophylaxis and control of this disease.